2022
DOI: 10.2355/isijinternational.isijint-2021-366
|View full text |Cite
|
Sign up to set email alerts
|

<i>δ</i>–pearlite Reaction by Carburization in Fe–Cr Binary Alloy

Abstract: The eutectoid transformation of δ -ferrite → γ -austenite + carbide by carburization was studied comprehensively with Fe-Cr binary alloy. It was observed that δ -pearlite consisted of γ -austenite and M 23 C 6 carbide formed with unidirectional lamellar structure parallel to the carburization direction, and consequently the γ -austenite transformed to α'-martensite on quenching. The reconstruction of the parent γ -austenite orientation revealed that the both of austenite and M 23 C 6 phases have a preference g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…On the other hand, formation of ( + Si 3 N 4 ) lamellar in the Fe-1Si alloy is, at least to the authors' knowledge, the first to be observed in the austenitic nitriding treatment. A similar reaction occurs during carburizing of alloy steels and is known as -pearlite transformation forming by eutectoid transformation [30][31][32][33][34] . Fig.…”
Section: Alloying Effects On Microstructure Evolutionmentioning
confidence: 98%
“…On the other hand, formation of ( + Si 3 N 4 ) lamellar in the Fe-1Si alloy is, at least to the authors' knowledge, the first to be observed in the austenitic nitriding treatment. A similar reaction occurs during carburizing of alloy steels and is known as -pearlite transformation forming by eutectoid transformation [30][31][32][33][34] . Fig.…”
Section: Alloying Effects On Microstructure Evolutionmentioning
confidence: 98%